The good, the bad, and the ugly - Rennie, Eloise Nadine (Rhodes University, 2026)
The aim of this study was to explore how receiving a late diagnosis of Autism Spectrum Disorder (ASD)¹ impacts an individual's sense of identity and belonging. Through a qualitative methodology using online surveys and semi-structured interviews, the study investigates how diagnosis functions as a transformative life event. Grounded in Victor Turner’s concepts of liminality and communitas, diagnosis is conceptualised as a contemporary rite of passage initiating a process of identity rupture, reflection, and reintegration. The findings revealed that diagnosis often follows a prolonged period of emotional distress and social disconnection. While initially destabilising, the diagnosis offers a framework through which individuals can reflect on their past experiences with compassion leading to increased self-understanding, coping mechanisms, boundary-setting, and the formation of meaningful connections with other autistic individuals. The sense of communitas that the meaningful and affirming relationships provide offers emotional solidarity during the transition into a more authentic self. The study contributes to the growing body of literature that centres autistic voices and highlights the need for more accessible, affirming, and timely diagnostic pathways for adults. It positions late diagnosis as the beginning of an ongoing and powerful journey toward self-acceptance and belonging.
finding self and belonging after a late diagnosis of Autism Spectrum Disorder
Keywords: Uncatalogued